Dynamic investigation on the Mirandola bell tower in post-earthquake scenarios - Zanotti Fragonara, Luca; Boscato, Giosue; Ceravolo, Rosario; Lentile, Silvia; Russo, Salvatore; Pecorelli, Marica Leonarda; Quattrone, Antonino (Springer, 2016)
After the seismic events of the 20th and 29th of May 2012 in Emilia (Italy), most of the monumental and historic buildings of the area were severely damaged. In a few structures, partial collapse mechanisms were observed (e.g. façade tilting, out-of-plane overturning of panels…). This paper presents the case-study of the bell tower of the Santa Maria Maggiore cathedral, located in Mirandola (Italy). The dynamic response of the structure was evaluated through operational modal analysis using ambient vibrations, a consolidated non-destructive procedure that estimates the dynamic parameters of the bell-tower. The dynamic tests were carried out in pre-intervention and post-intervention conditions in order to understand the sensitivity of dynamic measurements to safety interventions. Furthermore, a comparative study is made with similar cases of undamaged masonry towers up to the 6th mode. Finally, an investigation on the state of connections and of the building itself is carried out via FE model updating.
Keywords: structures; cultural heritage; structural identification; model updating; post-earthquake safety intervention; vibration methods; 2012 Emilia earthquake